2022
DOI: 10.3389/fneur.2022.1087969
|View full text |Cite
|
Sign up to set email alerts
|

EEG as an indispensable tool during and after the COVID-19 pandemic: A review of tribulations and successes

Abstract: During the coronavirus disease 2019 (COVID-19) pandemic, elective and non-emergent tests and procedures were delayed or suspended in lieu of diverting resources to more emergent treatment of critically ill patients and to avoid the spread and contraction of COVID-19. Further, the workforce was stretched thin, and healthcare facilities saw high turnover rates for full-time and contract employees, which strained the system and reduced the ability to provide clinical services. One of the casualties of these chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…However, these findings should be interpreted with caution, as they may be influenced by the substantial obstacles that patients with epilepsy face in obtaining medication and care in various ways, despite the implementation of telehealth guidance during the pandemic ( Rasmusson and Hartshorn, 2005 ; Mueller et al, 2021 ; Pellinen and Holmes, 2022 ). Additionally, the constrained availability of Electroencephalogram (EEG), particularly in epilepsy monitoring units, during the pandemic has compelled the exploration of alternative diagnostic methods, which may have implications for the precise diagnosis of epilepsy and its subtypes ( Freund and Feyissa, 2022 ). In this study, we utilized epilepsy and its subtypes, including focal and generalized epilepsy, as the exposure variables to investigate the potential causal effect of epilepsy on COVID-19 using the MR method.…”
Section: Discussionmentioning
confidence: 99%
“…However, these findings should be interpreted with caution, as they may be influenced by the substantial obstacles that patients with epilepsy face in obtaining medication and care in various ways, despite the implementation of telehealth guidance during the pandemic ( Rasmusson and Hartshorn, 2005 ; Mueller et al, 2021 ; Pellinen and Holmes, 2022 ). Additionally, the constrained availability of Electroencephalogram (EEG), particularly in epilepsy monitoring units, during the pandemic has compelled the exploration of alternative diagnostic methods, which may have implications for the precise diagnosis of epilepsy and its subtypes ( Freund and Feyissa, 2022 ). In this study, we utilized epilepsy and its subtypes, including focal and generalized epilepsy, as the exposure variables to investigate the potential causal effect of epilepsy on COVID-19 using the MR method.…”
Section: Discussionmentioning
confidence: 99%
“…The resumption of EEG began with the A) implementation of guidelines, to help deal with both non-COVID related prior/incident neurological conditions [9,[32][33][34][35][36][37][38][39][40][41][42][43][44][45] and B) the neurological sequelae due to para-and post-COVID, medication toxicity related to COVID treatment and post-COVID vaccination sequelae [11,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64].…”
Section: The Tipping Pointmentioning
confidence: 99%
“…Implementation of COVID appropriate safety guidelines and EEG protocols are mentioned below: [9,[32][33][34][35][36][37][38][39][40][41][42][43][44][45] i. Good medical practice (GMP) hygiene guidelines were defined and established ii.…”
Section: A)mentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic has significantly complicated the process of recording electrical brain activity, particularly the isolation measures required [15]. Other repercussions of the pandemic include less access to participants, difficulty in collecting data, and limited recruitment [16]. Be that as it may, some EEG work performed during prolonged isolation periods has reported that there seems to be decreased alpha power in the restingstate EEG [17].…”
Section: Introductionmentioning
confidence: 99%